(untitled) (Indian Journal of Pure & Applied Physics (IJPAP), 2024)
In present work, the Copper doped Nickel Oxide nanoparticles with molar concentrations (0%, 5%, 10% & 20%) were synthesized by microwave irradiated chemical co precipitation protocol and thereafter, calcination, the required nano-crystalline materials samples were examined through various techniques in order to make a comparative analysis of the magnetic behavior of pure Nickel Oxide nano-crystalline with various Copper doped Nickel Oxide nano-crystalline materials. The structural outcomes from X-Ray Diffractometer (XRD) tool and Fourier Transform Infar Red (FTIR) technique shows that FCC crystalline structure of NiO occurs. The crystallite size was determined using Debye Scherer formula and average crystallite size was 36.35nm for un-doped NiO nano particles whereas on addition the content of doping the crystallite size varies from 37.38nm for Cu 5%, 36.10nm for Cu 10% and 28.07nm for Cu 20% at when calcined at 600 °C temperature for 2 hours respectively. The IR spectrum peaks at positions 478 cm-1were attributed by O-Ni-O vibration whereas peak at 567 cm-1and 687cm-1 were assigned to O-Cu-O vibrations of CuO & Cu2O crystalline respectively.VSM results of various calcined samples with different dopant concentrations reveals that the behaviors of nanoparticles were ferromagnetic in nature with small hysteresis loss. However, the remarkable changes were noticed in saturated magnetization intensity with Cu2+ ion concentration in NiO lattice structure. The Cu 10% concentration doped NiO nanostructure materials were recommended as key materials for electromagnetic formation for MRI equipment applications with high range of applied magnetic field.